The Technology for Financial Inclusion to Strengthen Women’s Economic Empowerment in China and Indonesia - Aziz, Muhammad; Ramdlaningrum, Herni; Salim, Agus (Fast in Social Sciences, 2025)
Throughout the globe, women's access to finance is disproportionally less than men's. However, technology's emergence has allowed women to strengthen financial inclusion. The combination of digitalization and internet connection has born financial technology (Fintech), which all can access. This paper discusses the impact of Fintech in strengthening financial inclusion as a means for women's economic empowerment through the analysis of Fintech development in China and Indonesia. This paper selects Indonesia and China as both countries have similar proliferation on Fintech, and to some extent, both Fintech developments are influenced by one another. This paper uses a literature review methodology to explore Fintech development and practices that occurred in the two countries. This paper uses published journals, reports, and online articles as primary sources.